Determinant Implementation of Accounting Digitalization in MSMEs - Feby Millenia Itsnaini; Doddy Setiawan; Y Anni Aryani (The Asian Journal of Technology Management (AJTM), 2024)
Abstract: This research was conducted with the aim of determining the influence of relative advantage, organizational readiness, effort expectations and facilitating conditions on the implementation of accounting digitalization using a sampling technique, namely purposive sampling. This research was obtained in the form of primary data using collection techniques through questionnaires with a total of 116 MSME respondents in the city of Surakarta. The research method used is quantitative with data analysis techniques, namely variant-based Structural Equation Modeling (SEM). The data that has been collected is analyzed using SmartPLS 4. The results of this research find that expectations of efforts and facilitating conditions have a positive effect on the implementation of accounting digitalization, which means that accounting digitalization provides convenience and adequate facilities. Meanwhile, relative superiority and organizational readiness have a negative effect on the implementation of accounting digitalization, which means that MSME players feel that accounting digitalization does not provide adequate information for their business processes. The implication of the results of this research is to encourage the government to support the use of digital accounting among MSMEs by providing training in the form of socializing the use of new applications or technology to simplify the process of managing business finances. Keywords: Accounting digitalization, MSME, relative advantage, organizational readiness, expected effort